2013
DOI: 10.1016/j.virol.2013.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Genetic recombination of tick-borne flaviviruses among wild-type strains

Abstract: Genetic recombination has been suggested to occur in mosquito-borne flaviviruses. In contrast, tick-borne flaviviruses have been thought to evolve in a clonal manner, although recent studies suggest that recombination occurs also for these viruses. We re-analyzed the data and found that previous conclusions on wild type recombination were probably falsely drawn due to misalignments of nucleotide sequences, ambiguities in GenBank sequences, or different laboratory culture histories suggestive of recombination e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 39 publications
2
28
0
5
Order By: Relevance
“…All three subtypes are known to co-circulate in areas where the geographical ranges of I. ricinus and I. persulcatus overlap [14,15]. The European subtype is the only subtype so far found in ticks in Sweden [16-18], Norway [19] and Denmark [20]. In Finland, both the European and Siberian viruses have been detected in I. persulcatus .…”
Section: Introductionmentioning
confidence: 99%
“…All three subtypes are known to co-circulate in areas where the geographical ranges of I. ricinus and I. persulcatus overlap [14,15]. The European subtype is the only subtype so far found in ticks in Sweden [16-18], Norway [19] and Denmark [20]. In Finland, both the European and Siberian viruses have been detected in I. persulcatus .…”
Section: Introductionmentioning
confidence: 99%
“…Recombination between wild-type and attenuated vaccine strains and the putative consequences thereof have been demonstrated and/or discussed for several viruses, such as members of the Flaviviridae family (34)(35)(36), pestiviruses (37), polioviruses (38)(39)(40), avian paramyxovirus-1 (41), myxoma viruses (42), porcine reproductive and respiratory syndrome virus (43), and herpesviruses (15,22,44,45). Recombination between two live herpesvirus vaccine strains was reported for pseudorabies virus, which is an alphaherpesvirus that infects pigs (44).…”
mentioning
confidence: 99%
“…; Norberg et al. ), has not been shown experimentally for tick‐borne flaviviruses and is not discussed in this study. The rate of mutations in RNA viruses is high and estimated to be about 10 −2 –10 −5 nucleotide substitutions per site per year (Holmes ).…”
Section: Introductionmentioning
confidence: 76%
“…The only demonstrated mechanism of genetic variation in TBEV is a mutation process via single nucleotide substitutions. Recombination, although detected computationally (Bertrand et al 2012;Fajs et al 2012;Norberg et al 2013), has not been shown experimentally for tick-borne flaviviruses and is not discussed in this study. The rate of mutations in RNA viruses is high and estimated to be about 10 À2 -10 À5 nucleotide substitutions per site per year (Holmes 2009).…”
Section: Introductionmentioning
confidence: 79%